From Seafet And Asa: Precursors Of Asean - Tarling, Nicholas (Penerbit Universiti Sains Malaysia (USM Press), 2007)
With the disappearance of the imperial structures that had dominated Southeast Asia, newly-independent states had to develop foreign policies of their own. So far few, if any, have been willing to allow historians to explore the documentary evidence that has no doubt been preserved. Somewhat paradoxically, they must turn to the archives of external powers, which largely follow a thirty-year rule. Their diplomats were indeed often keenly interested in collecting information from ministers, on the golf course or otherwise, and from officials, who might convey or leak it more or less straightforwardly. In my recent book, Regionalism in Southeast Asia, I was able to incorporate material from United Kingdom (UK) records on the development of Southeast Asia Friendship and Economic Treaty (SEAFET), Association of Southeast Asia States (ASA) and Association of Southeast Asian Nations (ASEAN). I have been turning more recently to the material in the New Zealand archives, which contain not only reports from New Zealand diplomats but also from Australian and Canadian diplomats as well. They have both supported and modified my conclusions.